Preparation method of multi-component polysiloxane

By optimizing raw materials and reaction conditions, a polysiloxane with high reactivity, water resistance and durability was prepared, which solved the shortcomings of the polysiloxane preparation method in the prior art, met the needs of high-performance polysiloxane materials, and significantly improved the performance of rigid polyurethane foam.

CN119684611AActive Publication Date: 2025-03-25ADVANCED TECH RES INST OF BEIJING UNIV OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510133269.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-06
Publication Date
2025-03-25
Estimated Expiration
2045-02-06

AI Technical Summary

Technical Problem

The existing polysiloxane preparation methods have shortcomings in reaction efficiency, product purity, mechanical properties, durability and application range, and it is difficult to meet the modern industry's demand for high-performance polysiloxane materials.

Method used

By optimizing raw material selection and reaction conditions, cyclic siloxane, organosilane coupling agent and polyol are used as composite starting agents to perform negative pressure nitrogen replacement and deoxygenation and heating reactions, control the temperature and pressure in the kettle, and perform multiple dropping and maturation reactions, and finally obtain high-performance polysiloxane through post-treatment and purification.

Benefits of technology

It improves the reactive activity, water resistance and durability of polysiloxanes, and is suitable for the preparation of high-performance rigid polyurethane foam plastics, significantly improves the dimensional stability of the foam and reduces the thermal conductivity, and reduces the production cost and process control difficulty.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method and application of polypolysiloxane, and belongs to the technical field of polysiloxane preparation. The method comprises the following steps: putting cyclic siloxane, an organic silane coupling agent and polyhydric alcohol into a reaction kettle, and carrying out negative pressure nitrogen replacement deoxygenization and heating reaction; controlling the temperature in the kettle, respectively dropwise adding epichlorohydrin and epoxypropane, adding an acid catalyst, carrying out a curing reaction, removing unreacted monomers, and carrying out post-treatment to obtain a multi-component polysiloxane product. The polypolysiloxane prepared by the invention has high reaction activity, excellent water resistance and durability, and is suitable for preparation of high-performance rigid polyurethane foam plastic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic silicon materials, and specifically relates to a method for preparing multi-component polysiloxane. Background Art

[0002] With the widespread application of high-performance materials, polysiloxane, as an important organosilicon compound, has gradually become an important research object in the field of polymer materials due to its excellent heat resistance, weather resistance and low surface energy. However, the existing polysiloxane preparation method still has some shortcomings in reaction efficiency, product purity and application performance, which limits its wide application in industrial production.

[0003] Chinese patent CN101775141B provides a method for preparing castor oil-based polysiloxane polyols, which forms castor oil hydrosilylation products by reacting castor oil with pentamethyldisiloxane, and then reacts with cyclic siloxanes in an acid-catalyzed ring-opening reaction to finally prepare castor oil-based polysiloxane polyols. The method has a simple synthesis process and low cost. The obtained product greatly reduces the surface energy of the material without reducing the mechanical properties of the material, improves the water resistance of the material, and is particularly suitable for synthesizing waterborne polyurethane materials. However, in the technical scheme, the raw material selection and reaction condition control in the synthesis process are relatively simple, which may lead to limited room for improvement in reaction efficiency and product purity. In addition, the polyols prepared by the method have limited improvement in the mechanical properties and durability of the material while improving the surface properties of the material, and are difficult to meet certain high-end application requirements.

[0004] Another Chinese patent CN115594837B provides a method for preparing a modified polysiloxane polyol and its application. The invention prepares a polyether polyol product by mixing raw materials containing phenolic compounds and olamine compounds, heating them for reaction, adding propylene oxide and polyether-modified polysiloxane, performing nitrogen replacement and secondary reaction. The method improves the emulsification reaction efficiency of the polyol product in the foam reaction, significantly improves the fineness of the pores and reduces the surface bubbles of the rigid polyurethane foam. However, in the technical scheme, the reaction process is relatively complicated and there are many types of raw materials, which may lead to high production costs and greater difficulty in process control. In addition, while the polyol prepared by this method improves the foam performance, the overall performance and application range of the material are relatively limited, and it is difficult to meet the needs of certain special application fields.

[0005] Rigid foam is an important application form of polyurethane materials, especially in the field of building insulation materials and exterior walls. The proportion of polyurethane rigid foam in my country is 7%, while that in the United States is 65%, and there is still a lot of room for improvement. Secondly, the rapid development of cold chain logistics in my country will bring greater demand for rigid foam, while the application of refrigerators and electric water heaters is stable and improving. In the past 40 years, 141b has been the main foaming agent for polyurethane foam production in the fields of refrigerator insulation, pipeline insulation, energy-saving construction and furniture manufacturing. In order to meet the requirements of environmental protection, countries have conducted extensive research on alternative technologies. At present, the refrigerator industry mainly uses pentane foaming agents. Compared with the cyclopentane system, the n-pentane system can reduce the foam density by about 6%, and the low-boiling point n-pentane system can provide excellent processing performance and good fluidity, and has foam mechanical properties comparable to the cyclopentane system. However, due to the large number of bubbles on the surface of foam plastics made with n-pentane, the surface bubbles of the foam increase significantly compared with the cyclopentane system.

[0006] Therefore, it is particularly important to effectively improve the performance defects of n-pentane type composite materials in composite material applications. Therefore, the development of a modified polysiloxane polyol can effectively improve the dimensional stability of rigid polyurethane foam plastics made of n-pentane type composite materials and reduce the thermal conductivity. Therefore, the development of modified polysiloxane polyols for rigid foam systems is very urgent. The above problems show that the existing polysiloxane preparation methods still have certain deficiencies in terms of reaction efficiency, product purity, mechanical properties, durability and scope of application. Therefore, the present invention provides a method for preparing a polysiloxane, which improves reaction efficiency and product purity by optimizing raw material selection and reaction conditions, and at the same time greatly reduces the surface energy of the material without reducing the mechanical properties of the material, improves the water resistance and durability of the material, and meets the needs of modern industry for high-performance polysiloxane materials. Summary of the invention

[0007] The present invention aims to overcome the shortcomings of low reaction efficiency, low product purity, and limited improvement of mechanical properties and durability in the existing polysiloxane preparation method, and provides a preparation method and application of multi-polysiloxane. The multi-polysiloxane prepared by the present invention has high reactivity, excellent water resistance and durability, and is suitable for the preparation of high-performance rigid polyurethane foam plastics.

[0008] The method for preparing the polysiloxane of the present invention comprises the following steps: 1) Cyclic siloxane, organosilane coupling agent and polyol are put into the reaction kettle, the kettle is sealed, negative pressure nitrogen is replaced to deoxygenate, and heating is performed for reaction; 2) Control the temperature in the kettle, add epichlorohydrin continuously for the first time, control the material temperature and the pressure in the kettle during the reaction process, after the addition is completed, ripen the reaction, add the acid catalyst, seal the kettle, and perform negative pressure displacement deoxygenation operation; 3) Control the temperature in the kettle, and continuously add propylene oxide for the second time. During the reaction process, control the material temperature and the pressure in the kettle. After the addition is completed, ripen the reaction and remove the unreacted monomers. 4) Post-treatment and refining to obtain polysiloxane products.

[0009] The multi-polysiloxane product of the present invention has high reactivity, excellent water resistance and durability, and is suitable for the preparation of high-performance rigid polyurethane foam plastics. By using cyclic siloxane, organic silane coupling agent and polyol as composite initiator raw materials, a product with a hydroxyl value of 400-450 mg / KOH and a viscosity of 20000-35000 mPa·s can be obtained. The combination of the composite initiator exerts a synergistic effect, improves the efficiency of the multi-polysiloxane in the reaction, and the product has higher reactivity and better performance. The problem of poor mutual solubility of the components when a single component is added is solved, and the purity and reaction efficiency of the product are improved.

[0010] Among them: including the following raw materials in parts by weight: cyclic siloxane: 15-25 parts; organosilane coupling agent: 3-8 parts; polyol: 10-18 parts; epichlorohydrin: 6-15 parts; acid catalyst: 0.1-0.3 parts; propylene oxide: 50-70 parts. By optimizing the raw material ratio, the prepared polysiloxane has high reactivity, excellent water resistance and durability, which can meet the preparation requirements of high-performance rigid polyurethane foam plastics, significantly improve the dimensional stability of the foam and reduce the thermal conductivity. In addition, this raw material combination avoids the use of too many complex raw materials while ensuring high performance, reduces production costs and process control difficulties, and is suitable for large-scale industrial production.

[0011] The cyclic siloxanes include: one or more of cyclotrisiloxane, cyclotetrasiloxane, cyclopentasiloxane, and cyclohexasiloxane. These cyclic siloxanes can efficiently undergo ring-opening polymerization under the action of a catalyst, and the reaction conditions are mild and easy to control, thereby significantly improving production efficiency. The combination of different cyclic siloxanes can adjust the molecular structure and properties of the polysiloxane. For example, cyclotrisiloxane and cyclotetrasiloxane can provide good thermal stability and mechanical properties, while cyclopentasiloxane and cyclohexasiloxane can further improve the flexibility and durability of the product. By selecting different types of cyclic siloxanes, polysiloxanes suitable for a variety of application fields can also be prepared to meet the needs of different scenarios.

[0012] The organosilane coupling agent includes: one or more of γ-glycidyloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane. By using these organosilane coupling agents, not only can the molecular structure of the polysiloxane be optimized, but also the problem of poor mutual solubility of a single component can be effectively solved, and the purity and reaction efficiency of the product can be further improved, making it more suitable for the preparation of high-performance rigid polyurethane foam. Preferably, the organosilane coupling agent is γ-glycidyloxypropyltrimethoxysilane, and its epoxy group can undergo a cross-linking reaction with the hydroxyl group in the polyol, further enhancing the mechanical properties and water resistance of the product.

[0013] The polyols include one or more of glycerol, sorbitol, pentaerythritol, ethylene glycol, and diethylene glycol. These polyols are widely available, low in cost, and exhibit good compatibility and reactivity during the reaction, which can effectively improve the reaction efficiency and product purity. Preferably, the polyol is sorbitol or diethylene glycol. The flexibility and water resistance of the product can be adjusted to make it more suitable for the preparation of high-performance rigid polyurethane foam.

[0014] The acidic catalyst includes sulfuric acid and the like.

[0015] The temperature of the heating reaction in step 1) is 110°C to 150°C, and the time is 2 h to 4 h. This temperature and time combination can not only ensure the rapid progress of the reaction, but also avoid the occurrence of excessive side reactions, thereby improving the reaction efficiency and optimizing the product performance, ensuring the purity and stability of the product, and making its hydroxyl value and viscosity meet the design requirements. Preferably, the temperature of the heating reaction is 120°C to 130°C, and the time is 2.5 h to 3.5 h.

[0016] Step 2) The temperature in the kettle is 110°C to 150°C, the material temperature is 110°C to 160°C, the pressure in the kettle is 0.1 MPa to 0.5 MPa, and the aging time is 2 h to 4 h. The suitable temperature range provides sufficient heat energy for the ring-opening reaction of epichlorohydrin, ensuring that it can efficiently react with cyclic siloxane, organosilane coupling agent and polyol, while avoiding side reactions or decomposition caused by excessive temperature. Secondly, by controlling the pressure in the kettle, the reaction system can be further stabilized, the generation of impurities can be reduced, and the purity and quality of the product can be improved. The aging time of 2 to 4 hours ensures the full progress of the reaction while avoiding the performance degradation caused by excessive reaction. Under this process condition, not only the reaction efficiency is improved, but also the controllability of the reaction process is ensured.

[0017] Step 3) The temperature in the kettle is 120°C to 160°C, the material temperature is 120°C to 160°C, the pressure in the kettle is 0.1 MPa to 0.5 MPa, and the aging time is 2 h to 4 h. By optimizing the reaction conditions, the reactivity, water resistance and durability of the polysiloxane can be further improved to meet the needs of high-end applications such as high-performance rigid polyurethane foams.

[0018] Step 4) The post-treatment includes the following steps: lowering the temperature in the kettle to 70°C~90°C, adding alkali solution and water, stirring, adding activated clay, heating to 110°C~130°C, vacuum dehydration, controlling the pressure in the kettle at -0.09 MPa~-0.07MPa, detecting the moisture content below 0.1%, discharging, filtering, and obtaining a multi-polysiloxane product. The addition of alkali solution can neutralize the acidic catalyst used in the reaction, prevent the residual acid from corroding or degrading the product, thereby improving the stability and storage performance of the product; secondly, activated clay can adsorb impurities and low molecular weight by-products generated during the reaction, further improving the purity of the product. In addition, by strictly controlling the heating and vacuum dehydration steps, ensuring that the moisture content of the product is less than 0.1%, this is crucial to improving the reactivity, water resistance and durability of multi-polysiloxane, especially when used for high-performance rigid polyurethane foam plastics, it can reduce the pore defects in the foam and improve the dimensional stability and mechanical properties of the foam.

[0019] The multi-polysiloxane product has a hydroxyl value of 400 mg / KOH to 450 mg / KOH and a viscosity of 20000 mPa·s to 35000 mPa·s.

[0020] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses cyclic siloxane, organic silane coupling agent and polyol as composite initiator raw materials to obtain a product with a hydroxyl value of 400 mg / KOH to 450 mg / KOH and a viscosity of 20000 mPa·s to 35000 mPa·s. The combination of composite initiators exerts a synergistic effect, improves the efficiency of polysiloxane in the reaction, and the product has higher reactivity and better performance.

[0021] 2. This production process and formulation technology solves the problem of poor mutual solubility of components when a single component is added, and improves the purity and reaction efficiency of the product.

[0022] 3. The high hydroxyl value and high viscosity system of the polysiloxane of the present invention effectively increases the degree of crosslinking of the rigid polyurethane foam plastic product during the foaming process, and improves the dimensional stability and mechanical properties of the product.

[0023] 4. During the reaction of the polysiloxane prepared by the present invention with isocyanate black material, the foam produced has fine pores and uniform density distribution. The rigid polyurethane foam made therefrom has a smaller pore size and fewer surface bubbles, which significantly improves the water resistance and durability of the material. DETAILED DESCRIPTION

[0024] The present invention is further described below by means of specific embodiments, wherein Embodiment 1 is the best embodiment. Example 1

[0025] 15 parts of cyclotetrasiloxane, 5 parts of γ-aminopropyltriethoxysilane, 12 parts of glycerol, 12 parts of epichlorohydrin, 0.2 parts of sulfuric acid and 60 parts of propylene oxide are used as raw materials. First, the cyclotetrasiloxane, γ-aminopropyltriethoxysilane and glycerol in the above raw materials are weighed in proportion and put into the reactor. The reactor adopts a stainless steel reactor with an agitator and a heating device to ensure that the raw materials can be fully mixed and heated evenly during the reaction. The reactor is sealed and deoxygenated with negative pressure nitrogen displacement to ensure an oxygen-free environment in the reactor to prevent the raw materials from oxidizing at high temperatures and affecting the performance of the product. The specific operation of displacement deoxygenation is: reduce the pressure in the kettle to -0.09MPa, hold for 10 minutes, then slowly fill with nitrogen, restore the pressure in the kettle to normal pressure, repeat this operation 3 times, and completely discharge the oxygen in the kettle.

[0026] After the sealed kettle operation is completed, turn on the heating device, gradually raise the temperature in the kettle to 110°C, and keep it at this temperature for 2 hours for heating reaction. After the heating reaction is completed, the temperature in the kettle should be maintained in the range of 110°C~150°C, and epichlorohydrin is continuously added through the pipeline for 1 hour. During the dropwise addition, the temperature in the kettle is controlled to be 130°C, the material temperature is 140°C, and the pressure in the kettle is 0.3MPa. After the dropwise addition is completed, continue the aging reaction at 130°C for 3 hours. After the aging reaction is completed, add 0.2 parts of sulfuric acid as an acidic catalyst, seal the reactor again, and perform negative pressure nitrogen replacement deoxygenation to reduce the pressure in the kettle to -0.09MPa, maintain for 10 minutes, and then slowly fill with nitrogen to restore the pressure in the kettle to normal pressure. Repeat this operation 3 times to ensure an oxygen-free environment in the kettle.

[0027] After adding sulfuric acid, the temperature in the kettle is controlled to be 110℃~150℃, the material temperature is 140℃, the pressure in the kettle is 0.3MPa, and propylene oxide is continuously added through the pipeline for 1 hour. After the addition is completed, the aging reaction is continued at 140℃ for 3 hours. After the aging reaction is completed, the unreacted monomer is removed. The specific steps are: lower the temperature in the kettle to 100℃, open the condenser on the top of the kettle, and reduce the pressure in the kettle to -0.09MPa through the vacuum pump, and maintain it for 30 minutes to ensure that the unreacted monomer is completely removed.

[0028] After the monomer is removed, post-treatment and refining operations are performed. The temperature in the kettle is lowered to 80°C, and 20% sodium hydroxide solution and distilled water are added. The amount of sodium hydroxide solution added is 1% of the total mass of the raw materials, and the amount of water added is 20% of the total mass of the raw materials. Turn on the agitator and stir for 30 minutes to ensure that the alkali solution and water are fully mixed with the raw materials, neutralize the acidic catalyst, and terminate the reaction. Add activated clay, the amount of activated clay added is 1% of the total mass of the raw materials, and continue stirring for 30 minutes. The activated clay absorbs the residual substances in the reaction process to improve the purity of the product. Raise the temperature in the kettle to 120°C, turn on the vacuum device, reduce the pressure in the kettle to -0.09MPa, maintain for 30 minutes, and perform dehydration operation. After the dehydration operation is completed, the moisture content in the kettle is detected by a moisture detector to ensure that the moisture content is less than 0.1%. Discharge, filter out the activated clay and other residual substances through a filtration device, and finally obtain a multi-polysiloxane product. Example 2

[0029] 25 parts of cyclohexasiloxane, 8 parts of γ-glycidyloxypropyltrimethoxysilane, 10 parts of pentaerythritol, 8 parts of epichlorohydrin, 0.3 parts of sulfuric acid and 50 parts of propylene oxide are used as raw materials. The preparation steps are the same as those in Example 1, and the specific operating conditions are as follows: after cyclohexasiloxane, γ-glycidyloxypropyltrimethoxysilane and pentaerythritol are put into the reaction kettle, the kettle is sealed, and negative pressure nitrogen displacement deoxygenation is performed to reduce the pressure in the kettle to -0.09MPa, and the pressure is maintained for 10 minutes, and then nitrogen is slowly filled to restore the pressure in the kettle to normal pressure, and this operation is repeated 3 times. After the displacement deoxygenation is completed, the heating device is turned on, the temperature in the kettle is gradually raised to 150°C, and the heating reaction is maintained at this temperature for 3 hours. After the heating reaction is completed, epichlorohydrin is continuously added through the pipeline at 150°C for 1 hour. During the addition process, the temperature in the kettle is controlled to be 150°C, the material temperature is 160°C, and the pressure in the kettle is 0.5MPa. After the addition is completed, the aging reaction is continued at 150°C for 4 hours. After the aging reaction is completed, 0.3 parts of sulfuric acid is added as an acidic catalyst, the kettle is sealed again, and negative pressure nitrogen displacement is performed to deoxygenate, and the pressure in the kettle is reduced to -0.09MPa, maintained for 10 minutes, and then nitrogen is slowly filled to restore the pressure in the kettle to normal pressure. Repeat this operation 3 times to ensure an oxygen-free environment in the kettle.

[0030] After adding sulfuric acid, the temperature in the kettle is controlled to be 120℃~160℃, the material temperature is 150℃, the pressure in the kettle is 0.5MPa, and propylene oxide is continuously added through the pipeline for 1 hour. After the addition is completed, the aging reaction is continued at 150℃ for 4 hours. After the aging reaction is completed, the unreacted monomer is removed. The specific steps are: lower the temperature in the kettle to 100℃, open the kettle top condenser, and reduce the pressure in the kettle to -0.09MPa by the vacuum pump, and keep it for 30 minutes to ensure that the unreacted monomer is completely removed. After the monomer is removed, post-treatment and refining operations are carried out, the temperature in the kettle is lowered to 90℃, and 20% sodium hydroxide solution and distilled water are added. The amount of sodium hydroxide solution added is 1% of the total mass of the raw materials, and the amount of water added is 20% of the total mass of the raw materials. Turn on the agitator and stir for 30 minutes to ensure that the alkali solution and water are fully mixed with the raw materials, neutralize the acidic catalyst, and terminate the reaction. Add activated clay, the amount of activated clay added is 1% of the total mass of the raw materials, and continue stirring for 30 minutes. The activated clay absorbs the residual substances in the reaction process to improve the purity of the product. Raise the temperature in the kettle to 120°C, turn on the vacuum device, reduce the pressure in the kettle to -0.09MPa, and maintain it for 30 minutes to perform the dehydration operation. After the dehydration operation is completed, use a moisture detector to detect the moisture content in the kettle to ensure that the moisture content is less than 0.1%. Discharge the material, filter out the activated clay and other residual substances through a filtering device, and finally obtain a multi-polysiloxane product. Example 3

[0031] 20 parts of cyclotrisiloxane, 6 parts of β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 15 parts of ethylene glycol, 9 parts of epichlorohydrin, 0.2 parts of sulfuric acid and 65 parts of propylene oxide are used as raw materials. The preparation steps are the same as those in Examples 1 and 2, and the specific operating conditions are as follows: cyclotrisiloxane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane and ethylene glycol are weighed in proportion and put into the reactor, the reactor is sealed, and negative pressure nitrogen displacement and deoxygenation are performed, the pressure in the reactor is reduced to -0.09MPa, maintained for 10 minutes, and then nitrogen is slowly filled to restore the pressure in the reactor to normal pressure, and this operation is repeated 3 times. After the displacement and deoxygenation is completed, the heating device is turned on, the temperature in the reactor is gradually raised to 120°C, and the heating reaction is maintained at this temperature for 3 hours. After the heating reaction is completed, epichlorohydrin is continuously added through the pipeline at 120°C for 1 hour. During the addition process, the temperature in the kettle is controlled to be 120°C, the material temperature is 130°C, and the pressure in the kettle is 0.3MPa. After the addition is completed, the aging reaction is continued at 120°C for 3 hours. After the aging reaction is completed, 0.2 parts of sulfuric acid is added as an acidic catalyst, the reactor is sealed again, and negative pressure nitrogen displacement is performed to deoxygenate, and the pressure in the kettle is reduced to -0.09MPa, maintained for 10 minutes, and then nitrogen is slowly filled to restore the pressure in the kettle to normal pressure. Repeat this operation 3 times to ensure an oxygen-free environment in the kettle.

[0032] After adding sulfuric acid, the temperature in the kettle is controlled to be 130℃~150℃, the material temperature is 140℃, the pressure in the kettle is 0.3MPa, and propylene oxide is continuously added through the pipeline for 1 hour. After the addition is completed, the aging reaction is continued at 140℃ for 3 hours. After the aging reaction is completed, the unreacted monomer is removed. The specific steps are: lower the temperature in the kettle to 100℃, turn on the top condenser of the kettle, and reduce the pressure in the kettle to -0.09MPa by the vacuum pump, and keep it for 30 minutes to ensure that the unreacted monomer is completely removed. After the monomer is removed, post-treatment and refining operations are carried out, the temperature in the kettle is lowered to 85℃, and 20% sodium hydroxide solution and distilled water are added. The amount of sodium hydroxide solution added is 1% of the total mass of the raw materials, and the amount of water added is 20% of the total mass of the raw materials. Turn on the agitator and stir for 30 minutes to ensure that the alkali solution and water are fully mixed with the raw materials, neutralize the acidic catalyst, and terminate the reaction. Add activated clay, the amount of activated clay added is 1% of the total mass of the raw materials, continue stirring for 30 minutes, and use the activated clay to adsorb the residual substances in the reaction process to improve the purity of the product. Raise the temperature in the kettle to 120°C, turn on the vacuum device, reduce the pressure in the kettle to -0.09MPa, maintain for 30 minutes, and perform dehydration operation. After the dehydration operation is completed, use a moisture detector to detect the moisture content in the kettle to ensure that the moisture content is less than 0.1%. Discharge the material, filter out the activated clay and other residual substances through a filtering device, and finally obtain a multi-polysiloxane product. The hydroxyl value range of the obtained multi-polysiloxane product is 400~450mg / KOH, and the viscosity range is 20000~35000mPa·s.

[0033] It can be seen from the above examples that the preparation method of the present invention can produce polysiloxane with excellent performance under different raw material ratios and reaction conditions. The key to the present invention lies in the combination of the composite initiator. Through the synergistic effect of cyclic siloxane, organic silane coupling agent and polyol, the efficiency of polysiloxane in the reaction is improved, and a polysiloxane product with high hydroxyl value and high viscosity is obtained.

[0034] The polysiloxane product of the present invention is particularly suitable for the preparation of high-performance rigid polyurethane foam. In specific applications, the polysiloxane product can be used as one of the raw materials of rigid polyurethane foam, reacting with isocyanate black material to generate foam. For example, in the process of preparing rigid polyurethane foam, the polysiloxane product is first mixed with isocyanate black material in a certain proportion, and the mixing ratio can be adjusted according to specific application requirements. Generally, the mass ratio of the polysiloxane product to the isocyanate black material is 1:1.2~1.5. After mixing, the mixture is poured into a mold for foaming reaction. The temperature of the foaming reaction is generally 70~80°C, and the time is 3~5 minutes. In this process, the high hydroxyl value and high viscosity system of the polysiloxane product effectively increases the crosslinking degree of the foam during the foaming process, and improves the dimensional stability and mechanical properties of the product. At the same time, due to the excellent water resistance and durability of the polysiloxane, the prepared rigid polyurethane foam exhibits a smaller pore size and fewer surface bubbles during the application process, which significantly improves the water resistance and durability of the material.

[0035] In order to further verify the performance of the present invention, the following experiments were performed: Experiment 1: Take the polysiloxane product prepared in Example 1, mix it with isocyanate black material in a mass ratio of 1:1.2, pour it into a mold, and carry out a foaming reaction. The reaction temperature is 75°C and the reaction time is 4 minutes. After the foaming reaction is completed, take out the foam plastic sample and carry out a performance test. The test results show that the foam plastic has a pore size of 0.1mm, a surface bubble number of 10 / m², a uniform density distribution, good dimensional stability, excellent mechanical properties, good water resistance, and can still maintain more than 95% of the mechanical properties after being immersed in water for 48 hours.

[0036] Experiment 2: Take the polysiloxane product prepared in Example 2, mix it with isocyanate black material at a mass ratio of 1:1.3, pour it into a mold, and perform a foaming reaction. The reaction temperature is 75°C and the reaction time is 4 minutes. After the foaming reaction is completed, take out the foam plastic sample and perform a performance test. The test results show that the foam plastic has a pore size of 0.12mm, a surface bubble number of 8 / m², a uniform density distribution, good dimensional stability, excellent mechanical properties, good water resistance, and can maintain more than 96% of the mechanical properties after being immersed in water for 48 hours.

[0037] Experiment 3: Take the polysiloxane product prepared in Example 3, mix it with isocyanate black material at a mass ratio of 1:1.4, pour it into a mold, and perform a foaming reaction. The reaction temperature is 75°C and the reaction time is 4 minutes. After the foaming reaction is completed, take out the foam plastic sample and perform a performance test. The test results show that the foam plastic has a pore size of 0.1mm, a surface bubble number of 12 / m², a uniform density distribution, good dimensional stability, excellent mechanical properties, good water resistance, and can maintain more than 95% of the mechanical properties after being immersed in water for 48 hours.

[0038] It can be seen from the above experimental results that the multi-polysiloxane product prepared by the present invention exhibits excellent comprehensive performance in the process of preparing rigid polyurethane foam plastics by reacting with isocyanate black material. The foam plastic has small cell size, small number of surface bubbles, uniform density distribution, good dimensional stability and mechanical properties, and significantly improved water resistance, and is suitable for the preparation of high-performance rigid polyurethane foam plastics.

[0039] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a polysiloxane, characterized in that: The following steps are involved: 1) Prepare the following materials by weight: 15-25 parts of cyclic siloxane; 3-8 parts of organosilane coupling agent; 10-18 parts of polyol; 6-15 parts of epichlorohydrin; 0.1-0.3 parts of acid catalyst; 50-70 parts of propylene oxide; put the cyclic siloxane, organosilane coupling agent and polyol into a reaction kettle, seal the kettle and heat for reaction; 2) Epichlorohydrin is continuously added dropwise under heating. During the reaction, the temperature in the kettle is 110℃~150℃ and the pressure in the kettle is 0.1MPa~0.5MPa. After the addition is completed, the aging reaction is continued for 2h~4h, an acid catalyst is added, and the kettle is sealed to remove oxygen by negative pressure displacement; 3) Continuously add propylene oxide under heating. During the reaction process, the temperature in the kettle is controlled at 120°C ~ 160°C and the pressure in the kettle is controlled at 0.1 MPa ~ 0.5 MPa. After the addition is completed, the reaction is aged for 2 h ~ 4 h to remove the unreacted monomers; and then the multi-polysiloxane product is obtained through post-treatment.

2. The method for preparing polysiloxane according to claim 1, characterized in that: The cyclic siloxane includes one or more of cyclotrisiloxane, cyclotetrasiloxane, cyclopentasiloxane and cyclohexasiloxane.

3. The method for preparing polysiloxane according to claim 1, characterized in that: The organic silane coupling agent includes one or more of γ-glycidyloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.

4. The method for preparing a polysiloxane according to claim 1, characterized in that: The polyols include one or more of glycerol, sorbitol, pentaerythritol, ethylene glycol and diethylene glycol.

5. The method for preparing polysiloxane according to claim 1, characterized in that: The acidic catalyst includes sulfuric acid.

6. The method for preparing polysiloxane according to claim 1, characterized in that: The temperature of the heating reaction in step 1) is 110-150° C. and the time is 2-4 hours.

7. The method for preparing a polysiloxane according to claim 1, characterized in that: Step 3) The post-treatment comprises the following steps: lowering the temperature in the kettle to 70°C-90°C, adding alkali solution, water and activated clay under stirring and maintaining for 30min-60min, raising the temperature to 110°C-130°C and vacuum dehydrating, controlling the pressure in the kettle at -0.09 MPa-0.07MPa, discharging and filtering when the moisture content is less than 0.1%, and obtaining a multi-polysiloxane product.

Citation Information

Patent Citations

  • Method for preparing castor oil-based polysiloxane polyol

    CN101775141B

  • Preparation methods and applications of modified polysiloxane polyols

    CN115594837B

  • Tannin extract-based polyurethane rigid foam as well as preparation method and application thereof

    CN111217977A

  • Preparation method of inorganic nano composite polyether polyol

    CN113754880A

  • Preparation method of high-functionality alcohol amine polyether polyol

    CN116253868A